The relationship between interpersonal communication, physician competence, and work commitment with the effectiveness of internship programs in Jambi Province - Suriani, Nindia; Risnita, Risnita; MY, Mahmud (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to examine the relationship between interpersonal communication, physician competence, and work commitment to the effectiveness of internship programs in Jambi Province. This study uses a quantitative approach with a survey method, and involves 60 respondents who are participants in the internship program. The data analysis technique used was correlation analysis with a significance level of α = 0.05. The results of the study showed that there was a partial positive relationship between interpersonal communication, physician competence, and work commitment with the effectiveness of the internent program. Simultaneously, the trhee variables also had a significant influence on the F table of 4.01. These findings show that the effectiveness of the implementation of the internship program is greatly influenced by the quality of interpersonal communication, professional competence , and the work commitment of the magical participating doctors. The implications of this study show the need to increase interpersonal capacity, professionalism, and work loyalty of doctors to maximize the results of internship programs as an integral part of education and health services in Indonesia.